Pengaruh Modal dan Pinjaman terhadap Pendapatan KUD Mina Passabu Karya di Desa Panaikang Kec. Sinjai Timur - Nurhaedah Nurhaedah; akbar Akbar; Ansar Ali (Fakultas Ekonomi Universitas Indonesia Timur, 2021)
This study aims to determine the effect of capital and loans on the income of KUD Mina Passabu Karya. in Panaikang village, East Sinjai District, Sinjai Regency, South Sulawesi, the source of research data is the financial reports of KUD Mina Passabu Karya for the last 5 years from 2015 to 2019. Data Collection Techniques, Documentation, Research Instruments Financial report documents of Mina Passabu Karya KUD income for the last 5 years, starting in 2015 until the last year, 2019. The results of the Capital Variable research in this study have a significant effect on income. Partial T test of SPSS Coefficients output table which has a significance value (Sig) of 0.005. Research variables, Capital (X1), Loans (X2) and there is a significant effect of Capital Variables on Income. Loan variables in this study have a significant effect on income. Partial T test of SPSS Coefficients output table which has a significance value (Sig) of 0.024. Because the value of Sig. 0.024 > 0.05, it can be concluded that there is a significant effect of the Loan Variable (X2) on Income (Y). The capital and loan variables in this study have a simultaneous effect on income. F test which has a significant value (Sig) of 0.009. Because the value is 0.009 > 0.05, it can be concluded that there is a significant effect of the Capital and Loan Variables on Income